Philosophy of marathon runs - Piotr Fajdek (University of Applied Sciences in Tarnow, Poland, 2020)
The inquiry concerns the role of philosophy in the modern sport. It brings the heritage of great philosophers closer and emphasizes their relationships with people practicing running. It describes the mental zone of participants in marathon races, their motives and feelings, about the sport. The purpose of this study, was to investigate Does sport and philosophy may have something in common? Two totally different branches at first sight, gives us a chance to have a closer look on themselves. A wider perspective on sport by philosopher, on one hand and on the other, - chance to deep search in the mental zone of the athlete. Surprisingly running and philosophy have a lot in common. Both of branches are recognized as difficult, but results achieved may be very satisfying. In both disciplines patience and commitment is needed, and success comes very slowly. Every man is a philosopher, cause every one of us believes in natural law. We all as a mankind can conclude which kind of life is the best for us. Therefore, many of people decided to consciously engage in physical activity. As a way to enrich their personality, the way to discover their own self. As a way to response to the stresses of everyday life. Below we can find short comparison of two worlds - one which covers human mind, and other human body.